Prediction of fatigue life in multibody systems considering the increase of dynamic loads due to wear in clearances. (June 2021) - Ordiz, M.; Cuadrado, J.; Cabello, M.; Retolaza, I.; Martinez, F.; Dopico, D.
Highlights: A method to study the effect of joint clearances on the fatigue life of machines. Stress and fatigue analyses added to calculation of joint clearance evolution. Consideration of joint clearances turns linear damage into exponential. A method based on popular commercial software to streamline its use in industry. Abstract: The evolution of clearances in the joints of mechanisms due to the effect of wear has been already extensively addressed. This work goes a step beyond and studies the impact of clearance increase in the fatigue life of the machine. Moreover, a simplified method based on popular commercial software is proposed to analyze the effect of clearance evolution on the service life of machines, that requires a low effort from the user, thus being a suitable tool for industry. The method is first validated against an example from the literature and, then, it is applied to a real industrial machine. Results show that clearances may have a great impact in the service life of machines and, hence, they must be taken into account when seeking to make predictions at the design stage.